Political Violence in twentieth-century Europe - Bloxham, Donald; Gerwarth, Robert (Cambridge University Press, 2011)
"This is a comprehensive history of political violence during Europe's incredibly violent twentieth century. Leading scholars examine the causes and dynamics of war, revolution, counterrevolution, genocide, ethnic cleansing, terrorism and state repression. They locate these manifestations of political violence within their full transnational and comparative contexts and within broader trends in European history from the beginning of the dissolution of the Ottoman Empire in the late nineteenth-century, through the two world wars, to the Yugoslav Wars and the rise of fundamentalist terrorism. The book spans a 'greater Europe' stretching from Ireland and Iberia to the Baltic, the Caucasus, Turkey and the southern shores of the Mediterranean. It sheds new light on the extent to which political violence in twentieth-century Europe was inseparable from the generation of new forms of state power and their projection into other societies, be they distant territories of imperial conquest or ones much closer to home"--